The Effect of Work Experience and Training Intensity on Teacher Work Ethics at Junior High Schools - Ahmad Sopian; Nunu Mahnun; Sohiron Sohiron (Education and Sociedad Journal, 2025)
Teachers' work ethic is an important factor in supporting professionalism and the quality of education. Work experience and intensity of training are thought to be factors that can influence the formation of teachers' work ethics in carrying out their duties and responsibilities as educators. This study aims to determine the effect of work experience (X1) and intensity of training (X2) on teachers' work ethics (Y) at the Az-Zuhra Group Foundation Junior High School in Pekanbaru City. This study uses a quantitative method. The population in this study were all 81 teachers of the Az-Zuhra Group Foundation Junior High School in Pekanbaru City. The sampling technique used a saturated sampling technique, so that the entire population was used as a research sample. Data collection was carried out through questionnaires, observation, and documentation. Data analysis used multiple linear regression analysis with the help of the SPSS program. The results showed that work experience (X1) had a significant effect on teachers' work ethics (Y) with a significance value of 0.028 < 0.05. Simultaneously, work experience (X1) and the intensity of attending training (X2) have a significant effect on teacher work ethics (Y) with a significance value of 0.030 < 0.05. The results of the determination coefficient analysis show an R Square value of 0.869, which means that 86.9% of the variation in teacher work ethics can be explained by work experience and the intensity of attending training, while the remaining 13.1% is influenced by other factors outside the research.